Ethical Violations and Their Effects on Public Accounting Firms:A Case Study of KAP XYZ - Deli Yansyah; Khairunnisa Rahmah; Agung Prabowo (Sebatik, 2026)
Ethical violations by external auditors may reduce audit quality and create risks of inappropriate audit opinions, particularly when audited financial statements are used by external parties such as creditors. This study was to analyze the process, causes, and effects of ethical violations in an anonymized audit engagement at KAP XYZ involving Bank X. The study used a qualitative retrospective case study approach. Data were collected through semi-structured interviews with two actual informants, namely a partner familiar with the accountability process and a junior auditor who participated in fieldwork, supported by document review, member checking, and source triangulation. The data were analyzed thematically by comparing interview codes with the Indonesian Public Accountant Professional Code of Ethics and relevant Standards on Auditing. The findings indicate violations of professional competence and due care in audit planning, fieldwork, and reporting. Inventory and receivables testing relied excessively on analytical procedures without sufficient alternative procedures. Time pressure, weak supervision, and limited audit evidence contributed to an inappropriate unmodified opinion. The case resulted in contract termination by Bank X, reputational damage, and restrictions on the responsible auditors.